Against Mental Imagery: William Fish on Imagination as Perceptual Experience (Refleksi: Jurnal Kajian Agama dan Filsafat, 2026)
This paper examines William Fish’s rejection of the mental imagery model in explaining perceptual experience. The mental imagery model, rooted in representationalist frameworks or indirect realism, views experience as the perception of internal images that function as copies of external objects. Conversely, Fish, through the framework of direct realism, rejects the role of internal representations and asserts that perceptual experience involves the direct presence of external objects within its phenomenal structure. This paper argues that whilst Fish’s anti-imagery position successfully critiques the representational model, this framework faces difficulties in explaining the stability of the object of experience, particularly in the case of non-visual experiences such as sound and smell. In such contexts, the object of experience is not always clearly present and directly identifiable, thereby undermining the claim regarding the direct presence of the object in experience. This research is a descriptive-argumentative literature study aimed at analysing texts from a conceptual-philosophical perspective. Consequently, this paper demonstrates that the rejection of the mental imagery model has not yet fully succeeded in providing an adequate explanation of the phenomenal structure of perceptual experience.